Advancing electrochemical jet machining through process monitoring and control - Bisterov, Ivan (2023)
Electrochemical jet machining (EJM) is a non-conventional surface texturing process based on the localised anodic dissolution of a metallic work piece under the influence of an impinging electrolyte jet and an applied electrical potential. Although the surface modification of metallic components through EJM has been widely researched, there is a limited understanding of the electrical response of the system and unexploited opportunities to utilise this for process monitoring and integrated surface measurement. The research presented in this thesis addresses this knowledge gap and investigates the development of on-machine metrology and advanced process control through electrical measurements of the electrolyte jet. The application of a high-frequency electrical excitation allowed the measurement of work piece surface topography through mapping jet resistance as a function of spatial coordinates without affecting the surface. The performance of this novel measurement system was evaluated by comparison against established measurement techniques and an analytical model describing the response was proposed. This was further applied to investigate the resistance during machining, and it was demonstrated that the removal depth can be correlated to the measured resistance in-process. This provides a route for real-time monitoring of the live process and implementation of closed-loop control. A method for automated tracking of the geometry of the work piece during machining based on the resistance was developed. The resolution of electrochemical jet machining and the jet-based surface characterisation methods presented in this thesis is constrained by the diameter of the jet. To address this limitation, a novel end-effector was developed that can constrict the electrolyte jet through the hydrodynamic effect of flow focusing, and its machining and measurement performance was characterised. It was demonstrated that the jet diameter can be reduced 79% with corresponding 54% reduction of machine kerf width. The tool size can be continuously varied in-process through a simple variation of process parameters as part of the machine control programme.